DESAIN SISTEM AKUAPONIK PADA KEGIATAN BUDIDAYA IKAN AIR TAWAR DI DESA WAAI, KABUPATEN MALUKU TENGAH - Elizabeth M. Palinussa; Jacobus W. Mosse; Jolen Matakupan; Mauren M. Pattinasarany; Daniel. G. Louhenapessy; Jacqueline M. F. Sahetapy (Jurnal Abdi Insani, 2023)
Large amounts of fish production will have an impact on the need for land area and water use. One of the designs used is an aquaponic model. The concept of the aquaponics model is efficiency in land use and saving water use, then it is used properly by aquatic plants to be able to grow from the results of unconsumed food waste and the results of fish metabolism so that the cultivation environment and water quality are clean. This activity was carried out so that the public could understand how to make an aquaponic model, then experiments were carried out on raising fish and vegetables. The method of implementing the activity is in the form of training in making models of aquaponic cultivation systems so that they can solve problems faced by the community, but previously material is provided to business groups to increase knowledge before implementing the creation of a series of aquaponic systems. The community is directly involved in making a series of aquaponic models for freshwater fish cultivation. The aquaponics model is one of the offers provided to be a solution so that sustainable food production can be carried out to meet people's basic needs. The system created in this activity is a media bed model because it is suitable for beginner businesses or household scale. The people of Waai village are beginners in running a business, so this system can be put into practice. Because it is space efficient, and the manufacturing costs are relatively cheap, the electricity used is small, all types of plants can be grown. After the design has been formed, the fish and vegetable rearing process is carried out and after two months the harvest is carried out. The community understands how to make an aquaponic system model and practices it in raising fish and vegetables so that they can be harvested. So the activities of freshwater cultivation business groups must continue to develop.